Design of Carbon Dioxide Levels Measurement in Human Expiration Using End Tidal Carbon Dioxide (EtCO2) Capnography Method - Fuadi, Rifky Maulana; Yulianto, Endro; Irianto, Bambang Guruh; Mishra , Abhishek (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
Asthma is a chronic respiratory disease that has become the main reason patients are always rushed to the hospital emergency department. Capnography is a new method for examining asthma by measuring CO2 levels released by the lungs. The aim of this research was to create an EtCO2 capnography device that is able to measure CO2 levels in patients with asthma or difficult breathing to assist doctors in determining the urgency of using a ventilator in a patient. The EtCO2 Capnography device used in the hospital uses a sensor that is expensive, but in this study, a CO2 gas sensor type Cozir-WX-20 was used at a low price. The research was conducted by utilizing a CO2 gas sensor type Cozir-WX-20 which read CO2 concentration in ppm value and a microcontroller as an analog to digital data processor to be displayed on the LCD. Sensor characterization was carried out to compare the side-stream and main-stream methods, response time readings, and the accuracy of the cozir sensor. The resulting data were taken from CO2 cylinders and medical air gas at various flow volume values and was connected to the Cozir sensor, EtCO2 main-stream patient monitors, and side-stream EtCO2 patient monitors. The resulting CO2 readings from CO2 tubes and medical water on the Cozir-WX-20 sensor and main-stream patient monitors obtained an error of 4.6%, namely at a CO2 concentration of 7% or 70,000 ppm and sensor accuracy is above 95%. As for the side-stream method, the reading error is 1.96% and 1.74% at a CO2 concentration of 6-7%. Sensor accuracy on the side-stream method cozir module is above 95%. Response time reading CO2 gas at a concentration of 1%-7% under 5 seconds.